Target alignment in the Shen-Guang II Upgrade laser facility. (19th March 2018) - Ren, Lei; Shao, Ping; Zhao, Dongfeng; Zhou, Yang; Cai, Zhijian; Hua, Neng; Jiao, Zhaoyang; Xia, Lan; Qiao, Zhanfeng; Wu, Rong; Ji, Lailin; Liu, Dong; et al.
Abstract : The Shen-Guang II Upgrade (SG-II-U) laser facility consists of eight high-power nanosecond laser beams and one short-pulse picosecond petawatt laser. It is designed for the study of inertial confinement fusion (ICF), especially for conducting fast ignition (FI) research in China and other basic science experiments. To perform FI successfully with hohlraum targets containing a golden cone, the long-pulse beam and cylindrical hohlraum as well as the short-pulse beam and cone target alignment must satisfy tight specifications (30 and $20~\unicode[STIX]{x03BC}\text{m}$ rms for each case). To explore new ICF ignition targets with six laser entrance holes (LEHs), a rotation sensor was adapted to meet the requirements of a three-dimensional target and correct beam alignment. In this paper, the strategy for aligning the nanosecond beam based on target alignment sensor (TAS) is introduced and improved to meet requirements of the picosecond lasers and the new six LEHs hohlraum targets in the SG-II-U facility. The expected performance of the alignment system is presented, and the alignment error is also discussed.